2014
DOI: 10.1186/s12905-014-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Fertility desire among HIV-positive women in Tigray region, Ethiopia: implications for the provision of reproductive health and prevention of mother-to-child HIV transmission services

Abstract: BackgroundThere is growing recognition of the difficult reproductive decisions faced by HIV-positive women. Studies in both resource-constrained and developed countries have suggested that many HIV-positive women continue to desire children in spite of their understanding of the possible risks that HIV poses. This study investigates the factors associated with fertility desire among HIV-positive women in Tigray region, Ethiopia.MethodsA cross-sectional survey was conducted among 964 HIV-positive women receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 29 publications
10
42
1
Order By: Relevance
“…Regarding WLWH with a partner living without HIV, eight studies found percentages between 43% and 84% . In one study, a similar proportion of HIV‐infected women (48%) and HIV‐uninfected women (42%) in serodiscordant couples reported desiring additional children .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding WLWH with a partner living without HIV, eight studies found percentages between 43% and 84% . In one study, a similar proportion of HIV‐infected women (48%) and HIV‐uninfected women (42%) in serodiscordant couples reported desiring additional children .…”
Section: Resultsmentioning
confidence: 99%
“…Some prior research has found a history of giving birth to be associated with decreased prospective childbearing intention among HIV-infected women (Abbawa et al, 2015; Asfaw and Gashe, 2014; Kawale et al 2014; Melaku et al, 2014). A study of HIV-infected Ghanaian women, however, found childbearing intention to be positively associated with a history of childbearing (Gyimah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, mother-to-child transmission (MTCT) accounts for 95% of childhood HIV infections. It poses a significant threat to child health and survival [11, 13, 15]. In 2013, there were an estimated 793,700 people living with HIV including 200,300 children and the paediatric HIV population.…”
Section: Introductionmentioning
confidence: 99%